Proceso atención de enfermería en paciente de 26 años con abdomen agudo. - Verdezoto Alencastro, Jhon Ilver (2021)
Acute abdomen is characterized by being a critical situation that causes a series of severe abdominal symptoms, some of the clinical manifestations are: acute abdominal pain, gastrointestinal alterations, repercussion on the general state, According to Martínez (2016), acute abdomen disease is closely related to related to the characteristics of abdominal pain. There are 3 types of pain that are related to the acute abdomen: visceral, somatic and referred. For adequate treatment, an immediate differential diagnosis must be established between pathologies that require medical treatment or emergency surgical resolution. The present clinical case study reflects the clinical symptoms of a 26-year-old female patient with a medical diagnosis of acute abdomen, during the physical evaluation and complementary examinations it is finished with a definitive diagnosis, appendicitis, the nursing staff applied the Care Process nursing, for the timely recovery of the patient.